Parallel Processing and Applied Mathematics
DOI: 10.1007/978-3-540-68111-3_48
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Heterogeneity on Asynchronous Panmictic Genetic Search

Abstract: Abstract. Research scientists increasingly turn to large-scale heterogeneous environments such as computational grids and the Internet based facilities to satisfy their rapidly growing computational needs. The increasing complexity of the scientific models and rapid collection of new data are drastically outpacing the advances in processor speed while the cost of supercomputing environments remains relatively high. However, the heterogeneity and unreliability of these environments, especially the Internet, mak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…The distributed algorithm utilizes an asynchronous master worker approach, which has been shown to provide performance and scalability over iterative approaches in evolutionary algorithms [58,59]. This approach provides an additional benefit in that it is automatically load balanced -workers request and receive new LSTM RNNs when they have completed training previous ones, without blocking on results from other workers.…”
Section: Distributed Aco Optimizationmentioning
confidence: 99%
“…The distributed algorithm utilizes an asynchronous master worker approach, which has been shown to provide performance and scalability over iterative approaches in evolutionary algorithms [58,59]. This approach provides an additional benefit in that it is automatically load balanced -workers request and receive new LSTM RNNs when they have completed training previous ones, without blocking on results from other workers.…”
Section: Distributed Aco Optimizationmentioning
confidence: 99%
“…It is implemented in C++ and MPI, allowing easy use on clusters and supercomputers, and also provides support for systems with multiple graphical processing units. Further, TAO has shown that performing evolutionary algorithms asynchronously can provide significant improvements to performance and scalability over iterative approaches [13,39]. TAO is open source and freely available on GitHub, allowing easy use and extensibility 1 , and the presented ACO strategy has been included in that repository.…”
Section: Optimization Software Data and Reproducibilitymentioning
confidence: 99%
“…The disruption depends on initial properties of the dwarf galaxy and on the gravitational potential of the Milky Way, which is primarily due to dark matter. Asynchronous evolutionary algorithms (AEAs) have been used successfully to find the optimal input parameters for the probabilistic sampling method [3], [4], [3], [5], [6], and this work expands these AEAs to find the optimal input parameters for the N-body simulations, which will in turn provide new understanding of the origin and structure of the Milky Way.…”
Section: Introductionmentioning
confidence: 99%